Appendix to The Health of Software Engineering Research - Lo, David; Zimmermann, Tom; Nagappan, Nachi (2014)
This appendix contains the full survey that we conducted in Microsoft (Appendix A) and the top-5 research ideas that were rated by developers, testers, and program managers, respectively (Appendix B).